THE EFFECTIVENESS OF USING PREVIEW, QUESTION, READ, REFLECT, RECITE AND REVIEW (PQ4R) TOWARD STUDENTS’ CRITICAL THINKING ABILITY ON READING COMPREHENSION - Terasne, Terasne; Sugianto, Nanang (IKIP Mataram, 2019)
This research was aimed at knowing the effectiveness of using Preview, Question, Read, Reflect, Recite and Review or PQ4R toward Students’ Critical Thinking Ability on Reading Comprehension at Second Grade Students at SMAN 1 Batulayar in Academic Year 2017/2018. This research was an experimental research and the design was quasi-experimental nonequivalent design pre-test post-test design. The sample all of students at Second Grade and the total number was 24 students in which consisted of two classes. Where II-A consisted of 12 students and II-B consisted of 12 students. The class divided into two groups, namely experimental group and Control group. The data was collected by using pre-test and pos-test. The instrument of this research used was reading test inform of multiple choice test. The technique that used to analysis the data was t-test formula. From the data analysis, it found that the result of t-test (1.41) was lower than t-table (1.714). The mean score of experimental group in post-test was (19.16) and the mean score of pre-test was (7.08). Based on the result of the research, it can be concluded that the used of PQ4R has not effective toward Students’ Critical Thinking Ability on Reading Comprehension at Second Grade Students of SMAN 1 Batu Layar in Academic Year 2018/2019.